Development and characterization of new optical fibre based radiation dosimeters / Mostafa Ghomeishi - Mostafa, Ghomeishi (2015)
For past few years, the optical fibre dosimetry has been started to significantly grow in different ionising radiation applications due to their inherent advantages in terms of dosimeter characteristics and capability are used as both real-time or off-line monitoring. Several case-studies reported characteristics of optical fibres under the different dosimeter aspects instant various radiation sources and wide ranges of doses. However, in most cases, commercial available optical fibres have been used, which provided lots of ambiguous in terms of dosimeter characteristics regarding to various fabrication process, materials doped and element concentrations used by different manufacturers. This study demonstrates characterisation of different home-made optical fibres where their fabrication parameters, doping elements and concentrations, and physical characteristics are varied in classical approaches to carefully address the main sources and factors that influence the sensitivity and characteristics of optical fibre dosimeters. For fair and consistency in analysis, a set of relatively fixed characterisation methods are adapted based on the availability and accessibility of resources; for instance, the study is performed based on thermoluminescence (TL) dosimeter with the main irradiation of MeV electron/photon within 0.5-10 Gy of applied dose. The study is benchmarked with a couple of commercial available standard single mode fibres and conventional used lithium-fluoride dosimeter family, i.e., TLD-100. The main effect of fibre structure/shape on performance of dosimeter is investigated by fabricating different types of undoped and doped optical fibres including capillary optical fibre, conventional cylindrical fibre, flat fibre (FF) and photonic crystal fibre (PCF). Performance of undoped fibres are compared with doped fibres; all items have been fabricated from the same Ge-doped preform. The TL response of capillary fibre can be significantly improved with our novel proposed FF, especially, if some dopant element exists in the collapsing region of FF. The effect of cylindrical and flat fibre size on TL response is thoroughly investigated by fabricating several different sizes of fibres with fixed and varying coreiii to-cladding ratios. For FFs, this is performed by considering different collapsing methods during fabrication process. It is shown that the effect of fibre size with fixed core-to-cladding ratio on TL response is insignificant for cylindrical fibre, but it is significant for FFs. The effect of Ge concentration on TL response of optical fibres is also investigated by fabricating ten fibre preforms with different concentrations. Furthermore, performance of the other rare elements doped in optical fibres are demonstrated. The study is furnished by providing discussion on structural defects with the aid of computational glow curve deconvolution (CGCD) analysis almost for every different optical fibres used.